2008
DOI: 10.1200/jco.2008.26.15_suppl.15643
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression in gastrointestinal stromal tumours

Abstract: Background: While it is well known that cyclooxygenase-2 (COX-2) expression is increased in colorectal adenoma and carcinoma, there is only limited information on its status in stromal tumours. Methods: Immunohistochemical COX-2 staining was performed on a total of 42 confirmed gastrointestinal stromal tumours (GISTs) in the Pathology Department of Gaziantep University and the findings were compared with various other parameters. Results: We found a statistically significant correlation between the tumor mitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A study by Sevinc et al investigated cyclooxygenase 2 (COX-2) expression in GIST. Their findings demonstrated that use of Cox-2 inhibitors, with or without Tyrosine Kinase inhibitors, may be helpful in the adjuvant setting in preventing or delaying recurrence (Sevinc et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sevinc et al investigated cyclooxygenase 2 (COX-2) expression in GIST. Their findings demonstrated that use of Cox-2 inhibitors, with or without Tyrosine Kinase inhibitors, may be helpful in the adjuvant setting in preventing or delaying recurrence (Sevinc et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In many cancers, the association of over-expression of COX-2 and tumor progression is established. Moreover, COX-2 expression may be correlated with cancer prognosis [ 32 ]. Therefore, COX-2 polymorphism has received widespread attention, and many meta-analyses have been reported to assess the relationship between the polymorphism and human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Medical oncologists are divided into two groups according to the cancer type they are treating: Oncologists and OncoloGISTs. Every patient with GIST is a new experience for a medical oncoloGIST [17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%